Old and New Players of Inflammation and Their Relationship With Cancer Development - Chavez-Dominguez, Rodolfo; Perez-Medina, Mario; Aguilar-Cazares, Dolores; Galicia-Velasco, Miriam; Meneses-Flores, Manuel; Islas-Vazquez, Lorenzo; Camarena, Angel; Lopez-Gonzalez, Jose S. (Frontiers in Oncology, 2021)
Pathogens or genotoxic agents continuously affect the human body. Acute inflammatory reaction induced by a non-sterile or sterile environment is triggered for the efficient elimination of insults that caused the damage. According to the insult, pathogen-associated molecular patterns, damage-associated molecular patterns, and homeostasis-altering molecular processes are released to facilitate the arrival of tissue resident and circulating cells to the injured zone to promote harmful agent elimination and tissue regeneration. However, when inflammation is maintained, a chronic phenomenon is induced, in which phagocytic cells release toxic molecules damaging the harmful agent and the surrounding healthy tissues, thereby inducing DNA lesions. In this regard, chronic inflammation has been recognized as a risk factor of cancer development by increasing the genomic instability of transformed cells and by creating an environment containing proliferation signals. Based on the cancer immunoediting concept, a rigorous and regulated inflammation process triggers participation of innate and adaptive immune responses for efficient elimination of transformed cells. When immune response does not eliminate all transformed cells, an equilibrium phase is induced. Therefore, excessive inflammation amplifies local damage caused by the continuous arrival of inflammatory/immune cells. To regulate the overstimulation of inflammatory/immune cells, a network of mechanisms that inhibit or block the cell overactivity must be activated. Transformed cells may take advantage of this process to proliferate and gradually grow until they become preponderant over the immune cells, preserving, increasing, or creating a microenvironment to evade the host immune response. In this microenvironment, tumor cells resist the attack of the effector immune cells or instruct them to sustain tumor growth and development until its clinical consequences. With tumor development, evolving, complex, and overlapping microenvironments are arising. Therefore, a deeper knowledge of cytokine, immune, and tumor cell interactions and their role in the intricated process will impact the combination of current or forthcoming therapies.